National Survey of Environmental Cleaning Among Thai Hospitals - Apisarnthanarak, Anucha (Open Forum Infect Dis, 2017)
BACKGROUND: We evaluated the practices used by Thai hospitals to clean/disinfect the hospital environment and identified factors associated with adherence to environmental cleaning/disinfection (ECD) practices. METHODS: From 1 January 2014 to 30 November 2014, we surveyed all Thai hospitals with >250 beds and an intensive care unit. We assessed whether hospitals had implemented protocols and checklists for ECD within patient care areas, the use of ECD audits, and the adherence of ECD checklists and protocols (high adherence defined as ≥75%). Multivariable regression was used to examine associations between hospital characteristics and existence of ECD protocols and checklists together with adherence levels. RESULTS: A total of 212 (86.5%) of 245 eligible hospitals responded. Overall, 90.6% (192/212 hospitals) implemented an ECD protocol, 55.2% (117/212) implemented an ECD checklist, and 43.4% (92/212) audited ECD adherence. Where implemented, high adherence to ECD protocols and checklists was documented in 57.1% (109/192) and 57.3% (67/117), respectively. The presence of a hospital epidemiologist was associated with implementing an ECD checklist (OR = 2.4; P = 0.01) and conducting ECD audits (OR = 3.2; P = 0.001). Strong hospital administration support for the infection control program was associated with high adherence to implemented ECD protocols (OR = 5.4; P < 0.001) and checklists (OR = 3.7; P = 0.005). CONCLUSION: While most Thai hospitals have implemented ECD protocols and checklists, adherence to ECD protocols and checklists, and conducting ECD audits remain suboptimal. Our study supports the role of a hospital epidemiologist and administrative support to enhance the ECD practices in this middle income country. DISCLOSURES: All authors: No reported disclosures.